ENFORCEMENT OF ENVIRONMENTAL LAW ON WASTE MANAGEMENT AS A FORM OF IMPLEMENTING THE PRINCIPLES OF GOOD ENVIROMENTAL GOVERNANCE (GEG) BASED ON CHARACTER - Elly Kristiani Purwendah; Daniel Joko Wahyono (Ganesha Law Review, 2024)
This research aims to find out how environmental law enforcement regarding waste management is implemented as a form of implementing the principles of good environmental governance (GEG) based on character values. This research uses a normative juridical research method with a type of approach, namely a statutory approach and a conceptual approach. The legal materials used are primary, secondary and tertiary legal materials, obtained by conducting literature studies. The research results show that waste management is currently still an unresolved problem. There are several laws and regulations that have a correlation with waste management in Indonesia, namely Law no. 32 of 2009 concerning Environmental Protection and Management and several other laws. Law enforcement in waste management refers to 3 legal systems which are a combination of components, namely structure, substance and culture. Regulations regarding environmental law enforcement regarding waste must also apply character values, so that the goal of environmental law enforcement can be achieved, namely creating a sustainable environment in order to achieve a just, orderly, prosperous and characterized society. Apart from that, related to law enforcement in waste management, it can be studied from 2 sides, namely preventive and repressive law enforcement. Law enforcement in waste management is also an embodiment of the government and local governments in implementing the principles of Good Environmental Governance with the aim of raising public awareness of a good and healthy environment.